YOUNG REBELS, INDIGENOUS PEASANTS AND INSTALLATION SPEECH CLASSES IN THE FIELDS OF CAUTÍN. MOVIMIENTO CAMPESINO REVOLUCIONARIO. (CHILE 1967-1973) - Cárcamo Hernández, Ovidio (Revista de Historia Social y de las Mentalidades, 2024)
The purpose of this article is to analyze the route  followed by some militants of the Movimiento  de Izquierda Revolucionaria (MIR), in the  framework of the Chilean Agrarian Reform  from 1967 to 1973 in the province of Cautín,  in southern of Chile. Furthermore we seek  to describe the bonding process between the  MIR and the indigenous peasantry relationship  that was born on Movimiento Campesino  Revolucionario (MCR) in the late 1970s, starting  a major crackdown on big land ownership, which  buzzed local employer groups, at least until the  1973 military coup. Moreover, we sought to  characterize those young people mostly from the  urban middle class, whose delivery MIR allowed  to create a mass front, rare in agrarian history of  Chile.
Keywords: Chile; agrarian reform; land tenure; Indigenous peasant